A new era of amyloidosis: the trends at a major US referral centre. (2nd October 2019) - Staron, Andrew; Connors, Lawreen H.; Ruberg, Frederick L.; Mendelson, Lisa M.; Sanchorawala, Vaishali
Abstract: Objective: To characterize the changing spectrum of amyloidosis classes, as well as patient demographics, at a major US referral centre. Patients and methods: A retrospective analysis was conducted of all referrals to the Amyloidosis Centre at Boston University and Boston Medical Centre over the last 3 decades. Results: A total of 3987 new patients with amyloidosis were evaluated between 1990 and 2018 with the average number of new cases per year increasing 2.5-fold during this period. Systemic immunoglobulin light-chain (AL) amyloidosis decreased in proportion with each decade from 77% to 69% to 50% of new cases. Meanwhile, ATTR amyloidosis increased from 12% to 16% to 29%, predominately due to more diagnosis of ATTRwt and ATTRV122I amyloidosis. Gender and race profile differences, while changing over the observed time period, persisted among amyloidosis patients. Conclusion: Amyloid diseases are more widely recognized and classes of amyloidosis, including ATTRwt and ATTRV122I, once considered rare are now increasingly diagnosed. These data likely reflect a national trend of increased amyloidosis awareness facilitated by accessible diagnostic approaches, emerging treatments, and coordinated educational initiatives. Trial registration: ClinicalTrials.gov identifier: NCT00898235.